Termites of oil palm on peat soil: a 10-year collection from Endau Rompin. - Faszly, R; Mohammad-Faris, M.E; Azizil -Aliman, M.M; Shapuraa, O; Annie-Nunis, A.B; Norman , K; Sajap , A.S.; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2011)
In 2003 , we published the first list of termites (20) species from an ex-felled peat soil oil palm plantation located to the northeast of Endau Rompin National Park. In this paper we present an annotated checklist from the same site based on collections of a decade (October 2001 to October 2011). The list provided here was generated from collections using various sampling methods in addition to only transect method where the first list was made.We can be certain that a total of 55 species of termites from five functional taxonomic groups can be found at this site. Status of the species from the initial list were revised and updated. The current list suggested that the total number of species known so far from a single oil palm plantation site converted from peat swamp forest in Malaysia was considerably higher compared to collections made by researchers from other sites. We propose comparative collections be made on termite assemblages from the natural forest particularly the peat swamp forest to contrast and underderstand the rate of species turnover from such forest converted to oil palm plantation.